The Effects of Code-switching on Teaching English from EFL Students’ Perspective - Sangar Othman Ibrahim. (Zanco Journal of Humanity Sciences)
The title of this academic study is ‘The Effects of Code-switching on Teaching English from EFL Students’ Perspective. The main purpose of this study is to shed light on the effects of code-switching in teaching. The main research questions of this study are what are the main purposes and benefits of code-switching in teaching?